Re-appraisal of thylacocephalans (Euarthropoda, Thylacocephala) from the Jurassic La Voulte-sur-Rhône Lagerstätte - Laville, Thomas; Forel, Marie-Béatrice; Charbonnier, Sylvain (European Journal of Taxonomy, 2023)
Thylacocephalans are enigmatic euarthropods, known at least from the Silurian to the Cretaceous. Despite remaining uncertainties concerning their anatomy, key features can be recognised such as a shield enveloping most of the body, hypertrophied compound eyes, three pairs of raptorial appendages and a posterior trunk consisting of eight up to 22 segments bearing appendages and eight pairs of gills. Well-known for its euarthropod diversity, the La Voulte-sur-Rhône Lagerstätte (Callovian, Middle Jurassic, France) has provided many remains of four thylacocephalan species so far: Dollocaris ingens, Kilianicaris lerichei, Paraostenia voultensis and Clausocaris ribeti. In this paper, we study the type material as well as undescribed material. The re-description of La Voulte thylacocephalans reveals an unexpected diversity, with the description of two new species, Austriocaris secretanae sp. nov. and Paraclausocaris harpa gen. et sp. nov., and of specimens of Mayrocaris, a taxon originally described from Solnhofen Lagerstätten. We also reassign Clausocaris ribeti to Ostenocaris. The reappraisal of La Voulte thylacocephalans also provides important insight into the palaeobiology of Thylacocephala. New key anatomical features are described, such as an oval structure or a putative statocyst, which indicate a nektonic or nektobenthic lifestyle. Finally, we document a juvenile stage for Paraostenia voultensis.